Some notes on a second-order random boundary value problem - Tchier, Fairouz; Vetro, Calogero (Nonlinear Analysis: Modelling and Control, 2017)
We consider a two-point boundary value problem of second-order random differential equation. Using a variant of the α-ψ-contractive type mapping theorem in metric spaces, we show the existence of at least one solution.